Preparation method of V-containing high-performance aluminum alloy material for additive manufacturing
By adding vanadium elements to the aluminum alloy and using selected laser melt forming technology, AlCuMgV aluminum alloy material with high room temperature and high temperature performance was prepared, which solved the problem that it was difficult to prepare high-performance aluminum alloys in traditional processes, and realized the aluminum-based composite material. High intensity performance at different temperatures, while reducing process complexity and energy consumption.
Patent Information
- Application Number
- CN202411338768.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
It is difficult to prepare complex shape three-dimensional composite materials with high room temperature and high temperature performance in traditional aluminum alloy manufacturing processes, and additive manufacturing aluminum alloys have reduced performance at high temperatures, and cannot have both room temperature and high temperature performance.
AlCuMgV original alloy powder is prepared by adding vanadium to the aluminum alloy powder containing copper and magnesium, and 3D printing is performed using selective laser melt molding technology to regulate the morphology and mechanical properties of Al-Mg-V intermetallic compounds, combined with Specific laser printing parameters are prepared.
It realizes that aluminum-based composite materials have high strength performance at both room temperature and high temperature, solving the problem that traditional processes cannot have both room temperature and high temperature performance. At the same time, the process is simple, time-consuming and low energy consumption.
Smart Images

Figure CN119242972A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of additive manufacturing of aluminum alloys to improve room temperature and high temperature performance, and in particular to a V-containing high-performance aluminum alloy material for additive manufacturing. Background Art
[0002] Aluminum alloy is the second most commonly used structural alloy after steel. Due to its low density (titanium alloy and iron alloy are 2 times and 3 times that of aluminum alloy, respectively), high specific strength, good formability, and abundant crustal resources, it meets the needs of many industrial fields such as automobile, aerospace, marine and military for advanced lightweight materials. Traditional manufacturing processes such as powder metallurgy and mechanical alloying usually involve multiple steps to prepare particle-reinforced aluminum-based composites from mixed powders before final solidification; stirring casting is to make composites by adding reinforcing particles to liquid metal, which has the advantages of easy control of matrix structure and simple operation. However, these traditional processes cannot meet the growing demand for manufacturing complex-shaped three-dimensional composite parts, and many challenges in traditional processing routes hinder their higher and deeper applications. Metal additive manufacturing uses computer-aided design, point-by-point and layer-by-layer scanning to prepare fully densified, high-performance metal parts. It is a potential and most promising alternative for manufacturing high-density aluminum-based composites with minimal defects.
[0003] The microstructures produced by metal additive manufacturing in metal materials usually have highly non-uniform grain geometry, subgrain dislocation structure and chemical segregation. In recent years, it has been widely studied in titanium-based alloys, nickel-based alloys, copper-based alloys, cobalt-based alloys, and aluminum-based alloys. However, when aluminum alloys are used in the field of additive manufacturing, they have a strong sensitivity to thermal cracking in 3D printing due to their long solidification interval; and the complex thermal history during layer-by-layer printing leads to high levels of residual stress, resulting in fewer types of aluminum alloys available in the field of 3D printing. The potential of aluminum alloys for additive manufacturing has not yet been fully developed, so an alloy design strategy is urgently needed to improve the printability-performance synergy of aluminum alloys.
[0004] At present, the commonly used strengthening phases in additive manufacturing are mainly divided into ceramic phase (in-situ synthesis, external addition) and alloy phase (eutectic phase, fine grain phase). As a hard phase, ceramic phase often leads to brittle failure fracture and has low bonding strength with the matrix; while in-situ alloying not only has strong bonding with the matrix, but also effectively avoids the problem of uneven distribution, so it has been widely studied. When alloying to improve the performance of aluminum alloys in additive manufacturing, it is mainly divided into two types: ① Refining the grains through peritectic reaction elements (Sc, Zr, Ti) as a heterogeneous nucleation site, reducing the formation of columnar crystals and cracks between columnar crystals; ② Forming a eutectic network through eutectic reaction elements (Cu, Ni, Mn), reducing grain boundary defects and providing good liquid backfill during the solidification of the terminal eutectic, reducing the minimum thermal strain at the end. However, the degree of grain refinement of eutectic strengthening is low, mainly through solute segregation to refine the grains, without introducing a large number of nucleation particles into the matrix. Fine grain strengthening can significantly refine the grain size and reduce the cracks between columnar crystals. It is an ideal way to eliminate molding defects and strengthen the alloy matrix.
[0005] At the same time, additively manufactured aluminum alloys are not only used in room temperature environments. When used above 200°C, the problem of strengthening phase coarsening is serious, and grain boundary coarsening reduces performance. How to use additive manufacturing technology to prepare high-density, low-defect room-temperature high-strength aluminum alloys while further maintaining high-temperature performance is a current research hotspot. Under this application demand, it is urgent to develop an additive manufacturing aluminum alloy preparation method that has both room temperature and high-temperature performance. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an additively manufactured aluminum alloy having both room temperature and high temperature performance. The technical solution is as follows:
[0007] A method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing, characterized in that it comprises the following steps:
[0008] (1) Preparation of composite materials:
[0009] Adding metallic vanadium to aluminum alloy powder containing copper and magnesium elements or aluminum alloy with copper and magnesium elements introduced or pure aluminum powder to prepare original alloy powder; the original alloy powder mainly contains AlCuMgV; the vanadium content is 1.8-3.5wt.%;
[0010] (2) Selective laser melting.
[0011] Furthermore, in step (1), the original alloy powder is obtained by mixing and dispersing in a three-dimensional mixer; or the original alloy powder is prepared by smelting and atomization.
[0012] Furthermore, the method of step (2) is: placing the original alloy powder obtained in step (1) into a selective laser melting printer for printing and molding, and the printing parameters are laser power 160~340W, laser scanning rate 600~1200mm / s, scanning line spacing 80~110μm, powder layer thickness 20~40μm, powder feed ratio 1.8-3.4, and laser interlayer rotation angle 0°~90°.
[0013] Furthermore, the aluminum alloy containing copper and magnesium elements is 2024 aluminum alloy.
[0014] Furthermore, in the aluminum alloy powder containing copper and magnesium elements, copper Cu: 3.8%-4.9%, magnesium Mg: 1.2%-1.8%.
[0015] The technical effect of the present invention is undoubted. Compared with the prior art, it has the following advantages:
[0016] (1) Al-Mg-V intermetallic compounds reinforced aluminum-based composites can be prepared in a controllable manner using additive manufacturing, and the material composition has been innovated to improve the mechanical properties of aluminum-based composites by additive manufacturing: by changing the ratio of aluminum, magnesium, and vanadium in the aluminum alloy powder and the relevant parameters of 3D printing (laser power, laser scanning rate, scanning line spacing, powder layer thickness, etc.), the morphology of Al-Mg-V intermetallic compounds and the mechanical properties of composites can be controlled.
[0017] (2) Compared with the existing reported additive manufacturing aluminum alloy materials that cannot have both room temperature and high temperature performance, the V-containing high-performance aluminum alloy material of this patent has both room temperature and high temperature performance: while maintaining good room temperature performance (tensile strength ~ 500MPa), it also has high high temperature performance of 200℃ (tensile strength ~ 315MPa) and 250℃ (tensile strength ~ 230MPa). This effectively solves the problem that aluminum-based composite materials cannot have both room temperature and high temperature performance.
[0018] (3) The preparation process is simple, easy to operate, and time-saving. At the same time, compared with the existing patented laser power of up to 340W, the laser power used is lower, energy consumption is reduced, and cost is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The room temperature stress-strain curves of the samples prepared in Examples 1 to 6 of the present invention and the 2024 aluminum alloy prepared by the same process.
[0020] Figure 2 The room temperature stress-strain curve of the sample prepared within the preferred parameter range of the present invention.
[0021] Figure 3It is the stress-strain curve of the sample prepared within the preferred parameter range of the present invention at 200°C and 250°C.
[0022] Figure 4 It is a light microscope image of the sample obtained during parameter screening of the present invention.
[0023] Figure 5 This is a TEM image of the in-situ synthesized Al-Mg-V of the present invention.
[0024] Figure 6 This is the EDS surface scanning element distribution diagram of the in-situ synthesized Al-Mg-V under TEM. DETAILED DESCRIPTION
[0025] We design to add vanadium to pure aluminum or aluminum alloy or to add copper and magnesium to form Al-Mg-V intermetallic compounds. The present invention is further described below in conjunction with the embodiments, but it should not be understood that the above subject matter of the present invention is limited to the following embodiments. Without departing from the above technical ideas of the present invention, various substitutions and changes are made according to the common technical knowledge and customary means in the field, which should all be included in the protection scope of the present invention.
[0026] Example 1 (4%, 250, 600)
[0027] In this embodiment, the preparation method of in-situ generated Al-Mg-V intermetallic compound comprises the following specific steps:
[0028] Weigh 20g of vanadium powder and 485g of 2024 aluminum alloy powder and place them in a 5L stainless steel tank. Use a three-dimensional mixer to mix and disperse for 18h, with a ball-to-material ratio of 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100℃ for 2h. Use a laser powder bed fusion 3D printer for additive manufacturing, with a laser power of 250W, a laser scanning rate of 600mm / s, a scanning line spacing of 90μm, a powder layer thickness of 30μm, and a laser interlayer rotation angle of 67° to obtain a composite material printing sample.
[0029] Example 2
[0030] In this embodiment, the preparation method of in-situ generated Al-Mg-V intermetallic compound comprises the following specific steps:
[0031] Weigh 15g of vanadium powder and 485g of 2024 aluminum alloy powder and place them in a 5L stainless steel tank. Use a three-dimensional mixer to mix and disperse for 16 hours, with a ball-to-material ratio of 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100°C for 2 hours. Use a laser powder bed fusion 3D printer for additive manufacturing, with a laser power of 250W, a laser scanning rate of 600mm / s, a scanning line spacing of 100μm, a powder layer thickness of 30μm, and a laser interlayer rotation angle of 67° to obtain a composite material printing sample.
[0032] Example 3
[0033] The difference from Example 1 is that:
[0034] 12.5g of vanadium powder and 487.5g of 2024 alloy powder were placed in a 5L stainless steel tank. The materials were mixed and dispersed in a three-dimensional mixer for 16 hours, with a ball-to-material ratio of 1:1. The mixed powder after three-dimensional mixing and dispersion was taken out, and the particle size was sieved with a 250-mesh sieve. The powder <250 mesh was placed in a vacuum oven and dried at 100°C for 2 hours. A laser powder bed fusion 3D printer was used for additive manufacturing, with a laser power of 250W, a laser scanning rate of 600mm / s, a scanning line spacing of 100μm, a powder layer thickness of 40μm, and a laser layer rotation angle of 67° to obtain a composite material printing sample.
[0035] Example 4
[0036] The difference from Example 1 is that:
[0037] The used vanadium powder is 10 g and the 2024 alloy powder is 490 g.
[0038] Example 5
[0039] The difference from Example 1 is that:
[0040] The used vanadium powder was 5 g and the 2024 alloy powder was 495 g.
[0041] Example 6
[0042] The difference from Example 1 is that:
[0043] Among the 3D printing parameters, the laser power is 160W and the laser scanning rate is 1200mm / s. 15g of vanadium powder and 485g of 2024 aluminum alloy powder are placed in a 5L stainless steel tank. The three-dimensional mixer is used to mix and disperse for 16 hours, and the ball-to-material ratio is 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100℃ for 2 hours. Use a laser powder bed fusion 3D printer for additive manufacturing, with a laser power of 160W, a laser scanning rate of 1200mm / s, a scanning line spacing of 100μm, a powder layer thickness of 40μm, and a laser layer rotation angle of 67° to obtain a composite material printing sample.
[0044] Example 7
[0045] The difference from Example 1 is that:
[0046] The used vanadium powder is 12.5g, the 2024 alloy powder is 487.5g, the laser power is 220W, and the laser scanning rate is 800mm / s. It is placed in a 5L stainless steel tank. The three-dimensional mixer is used to mix and disperse for 16 hours, and the ball-to-material ratio is 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100℃ for 2h. Additive manufacturing is performed using a laser powder bed fusion 3D printer, with a laser power of 220W, a laser scanning rate of 800mm / s, a scanning line spacing of 100μm, a powder layer thickness of 40μm, and a laser layer rotation angle of 67° to obtain a composite material printing sample.
[0047] Example 8
[0048] The difference from Example 1 is that:
[0049] The vanadium powder used was 12.5g, the 2024 alloy powder was 487.5g, the laser power was 220W, the laser scanning rate was 1000mm / s, and the powder layer thickness was 30μm. It was placed in a 5L stainless steel tank. The three-dimensional mixer was used to mix and disperse for 16 hours, and the ball-to-material ratio was 1:1. The mixed powder after three-dimensional mixing and dispersion was taken out, and the particle size was sieved with a 250-mesh sieve. The powder <250 mesh was placed in a vacuum oven and dried at 100°C for 2h. A laser powder bed fusion 3D printer was used for additive manufacturing, with a laser power of 220W, a laser scanning rate of 1000mm / s, a scanning line spacing of 100μm, a powder layer thickness of 30μm, and a laser interlayer rotation angle of 67° to obtain a composite material printing sample.
[0050] Example 9
[0051] The difference from Example 1 is that:
[0052] The used vanadium powder is 12.5g, the 2024 alloy powder is 487.5g, the laser power is 250W, the laser scanning rate is 1000mm / s, and the powder layer thickness is 30μm. Place it in a 5L stainless steel tank. Use a three-dimensional mixer to mix and disperse for 16h, with a ball-to-material ratio of 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100℃ for 2h. Use a laser powder bed fusion 3D printer for additive manufacturing, with a laser power of 250W, a laser scanning rate of 1000mm / s, a scanning line spacing of 100μm, a powder layer thickness of 30μm, and a laser interlayer rotation angle of 67° to obtain a composite material printing sample.
[0053] Example 10
[0054] The difference from Example 1 is that:
[0055] The used vanadium powder is 12.5g, the 2024 alloy powder is 487.5g, the laser power is 250W, the laser scanning rate is 800mm / s, and the powder layer thickness is 30μm. Place it in a 5L stainless steel tank. Use a three-dimensional mixer to mix and disperse for 16h, with a ball-to-material ratio of 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100℃ for 2h. Use a laser powder bed fusion 3D printer for additive manufacturing, with a laser power of 250W, a laser scanning rate of 800mm / s, a scanning line spacing of 100μm, a powder layer thickness of 30μm, and a laser interlayer rotation angle of 67° to obtain a composite material printing sample.
[0056] Embodiment 11
[0057] The difference from Example 1 is that:
[0058] The used vanadium powder is 12.5g, the 2024 alloy powder is 487.5g, the laser power is 220W, the laser scanning rate is 600mm / s, and the powder layer thickness is 30μm. Place it in a 5L stainless steel tank. Use a three-dimensional mixer to mix and disperse for 16h, with a ball-to-material ratio of 1:1. Take out the mixed powder after three-dimensional mixing and dispersion, sieve the particle size with a 250-mesh sieve, and dry the powder <250 mesh in a vacuum oven at 100℃ for 2h. Use a laser powder bed fusion 3D printer for additive manufacturing, with a laser power of 220W, a laser scanning rate of 600mm / s, a scanning line spacing of 100μm, a powder layer thickness of 30μm, and a laser interlayer rotation angle of 67° to obtain a composite material printing sample.
[0059] Table 1 Mechanical properties data under different compositions and printing parameters
[0060]
[0061]
[0062] From the statistics in Table 1, it is found that when the V content is low, the coarse columnar crystals of 3D printed aluminum alloy cannot be effectively eliminated, and there are many cracks and voids, resulting in poor mechanical properties. At the same time, when the V content is too high, although the tensile strength is high, too many intermetallic compounds are generated, which increases the brittleness, mainly brittle fracture, and significantly reduces the elongation. Only when the V content is controlled within a certain range, the defects of 3D printed aluminum alloy are effectively eliminated, the mechanical properties are improved, and at the same time, too many brittle phases are not generated, and the elongation remains high.
Claims
1. A method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing, characterized in that: The following steps are involved: (1) Preparation of composite materials: Adding metallic vanadium to aluminum alloy powder containing copper and magnesium elements or aluminum alloy with copper and magnesium elements introduced or pure aluminum powder to prepare original alloy powder; the original alloy powder mainly contains AlCuMgV; the vanadium content is 1.8-3.5wt.%; (2) Selective laser melting.
2. The method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing according to claim 1, characterized in that: In step (1), the original alloy powder is obtained by mixing and dispersing the materials in a three-dimensional mixer; or the original alloy powder is prepared by smelting and atomizing.
3. The method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing according to claim 1, characterized in that: The method of step (2) is: placing the original alloy powder obtained in step (1) into a selective laser melting printer for printing and molding, and the printing parameters are laser power 160-340W, laser scanning rate 600-1200mm / s, scanning line spacing 80-110μm, powder layer thickness 20-40μm, powder feed ratio 1.8-3.4, and laser interlayer rotation angle 0°-90°.
4. The method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing according to claim 1, wherein the aluminum alloy containing copper and magnesium elements is 2024 aluminum alloy.
5. The method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing according to claim 1, characterized in that: The aluminum alloy powder containing copper and magnesium elements comprises 3.8% to 4.9% copper and 1.2% to 1.8% magnesium.
6. The method for preparing a V-containing high-performance aluminum alloy material for additive manufacturing according to claim 1, characterized in that: In the original alloy powder prepared in step (1), the copper content is 1-10wt.%, and the magnesium content is 1-10wt.%.
Citation Information
Patent Citations
Process for manufacturing an aluminum alloy part
CN110573276A
Method for in-situ synthesis of MgAlB4 or MgAl2O4 whisker reinforced aluminum-based composite material in additive manufacturing
CN115430842A
Method for obtaining bimodal grains in additive manufacturing of aluminum alloy
CN116921702A
Preparation method of additive manufacturing in-situ TiC ceramic particle reinforced aluminum-based composite material
CN117753988A
Preparation method of additive manufacturing in-situ TiC ceramic particle reinforced aluminum-based composite material
CN118272704A
Cited By
Additive manufacturing Al-Cu-X eutectic phase reinforced aluminum alloy material
CN120138453A
An additively manufactured Al-Cu-X eutectic phase strengthened aluminum alloy material
CN120138453B